MODEL PERENCANAAN DAN PENGENDALIAN PRODUKSI DI INDUSTRI PENGOLAHAN BUAH CARICA (CARICA PUBESCENS) - Machfud Machfud; Abdurrafi Abdurrafi (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
The competition in the carica fruit processing industry is increasing, so that efforts are needed to increase production efficiency through good production planning and control (PPC). CV XYZ is one of the carica fruit processing companies which has PPC problems. PPC activities done intuitively and not systematically causing a decision in PPC is ineffective and production process is inefficient. Those problems can be resolved by developing a PPC model in accordance with CV XYZ’s business process. So, this research objective was to develop a PPC model at CV XYZ. The model consisted of four sub-models which were related to each other. The first sub-model was Sub-model of Demand Forecasting and the second sub-model was Sub-model of Carica Fruit Availability Forecasting. Those two sub-models used the Auto-regressive Integrated Moving Average (ARIMA). The third sub-model was Sub-model of Production and Packaging Planning using Integer Linear Programming (ILP). The fourth sub-model was Sub-model of Carica Fruit Inventory Control using Material Requirement Planning (MRP). PPC model can clarify the PPC system at CV XYZ and produce optimal plans. PPC model improves efficiency of total production cost up to 39.86% and total inventory cost up to 27.56%. Keywords: carica industry, model, optimal, production planning and control